FAKTOR-FAKTOR YANG MEMPENGARUHI STRESS SELAMA STUDY FROM HOME PADA ANAK USIA SEKOLAH KELAS 4-6 SD DI SDIT SALSABILA BEKASI - Sofia Aini Sayuti Putri (2021)
School age child is a child in the age range 6-12 years. School age is a time to gain basic knowledge and experience for successful adjustment to adult life in the future. During the study from home, school age children are prone to experience academic stress. Academic stress is stress caused by academic stressors in the teaching and learning process. The purpose of this study was to determine the factors that influence stress during the study from home, in school age children grades 4-6 elementary school at SDIT Salsabila Bekasi. The study design used in this study was cross sectional with a sample size of 79 people. The sampling technique used was stratified random sampling. The data were collected using an online questionnaire. The data analysis used was the chi square test with a significance level of ≤ 0.05. The results of this study indicate that 55.7% of respondents experienced academic stress. The results of statistical analysis showed that the factors of pressure to excel (p-value = 0.012), social status compulsion (p-value = 0.004), and parental pressure (p-value = 0.049) influenced stress during study from home, in school age children grades 4-6 elementary school while the factor of gender (p-value = 0.998), self-efficacy (p-value = 0.312) and hardiness (p-value = 0.162) did not affect stress during study from home, in school age children grades 4-6 elementary school. Therefore, school and parents were suggested not to put excessive academic pressure on their children while studying from home.